Stress and Diet Quality Among Ecuadorian Adults During the COVID-19 Pandemic. A Cross-Sectional Study - Abril-Ulloa, Victoria; Santos, Sueny Paloma Lima-dos; Morejón-Terán, Yadira Alejandra; Carpio-Arias, Tannia Valeria; Espinoza-Fajardo, Ana Cristina; Vinueza-Veloz, María Fernanda (Frontiers in Nutrition, 2022)
Objective: We investigate the association between Stress and Diet quality in Ecuadorian adults during the COVID-19 pandemic. Design: A cross-sectional study. Setting: Data was collected using a self-administered online survey, including for Stress variable was used the Perceived Stress Scale (PSS-14), and Diet quality was evaluated using the Global Diet Index (GDI) and socioeconomic variables. A linear regression model with restrictive cubic splines was used to investigate the association between stress and diet quality. Participants: Participants were recruited by convenience sampling.—a total of 2602 individuals. Most participants were female (68.57%), with a median age of 25 (IQR: 25, 37), and had university education (78.52%). Results: Stress was reported by 26.06% of the sample. The majority of individuals (75.79%) reported having a diet that needed changes or an unhealthy diet. Independently on biological sex, age, level of education, the ratio of people/room, economic allowance, and expenses for food, stress was statistically significantly associated with diet quality (p = 0.035). The association between stress and diet quality was inverse and nonlinear; higher stress levels were associated with poorer diet quality. The consumption of palatable foods associated with stress was not statistically significant. Conclusions: Stress is associated with poorer diet quality. Public health measures to improve the mental health and lifestyle of the population are needed during the lockdown of the pandemic.